The rejection of nuclear energy in Austria: An anti-nuclear-consensus achieved by a social movment? - Bayer, Florian (Momentum Quarterly, 2014)
The paper discusses the relationship between the rejection of nuclear technologies in Austria and the Austrian anti-nuclear movement. Rigorously rejecting nuclear technologies is considered a characteristic of Austrian national identity. Understood as deeply rooted in Austria’s population, “being anti-nuclear” is perceived to be Austrian because of Austria’s history, especially the controversy over the commissioning of the nuclear power plant in Zwentendorf. First the history of nuclear energy in Austria and the referendum on the commissioning of the nuclear power plant in Zwentendorf are revisited. Afterwards these events are contrasted with the discussion on nuclear energy within the Austrian national assembly in the following years. In doing so the paper reveals that the controversy continued until the explosion of the nuclear reactor in Chernobyl. The analysis of the last years of the nuclear controversy and its ending demonstrates how the contemporary rejection of nuclear technologies was mostly shaped by actors and specific dynamics of Austria’s two party system and corporatist bodies. The anti-nuclear-consensus is mostly the result of top-down processes and not the achievement of the anti-nuclear movement or “the Austrian population.”